Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1039/c5ra01146a
|View full text |Cite
|
Sign up to set email alerts
|

Study of ion dynamics in lanthanum aluminate probed by conductivity spectroscopy

Abstract: Conductivity Spectra of LaAlO3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 48 publications
(40 reference statements)
1
9
0
Order By: Relevance
“…The figures show a near linear dependence of these parameters on each other with a slope of almost unity indicating a power law dependence of dc on H of the form 𝜎 𝑡 ∝ 𝜔 𝐻 𝑛 where n is the slope of the graph. This implies that the dc and ac conductivity are correlated in AHR [57].…”
Section: Resultsmentioning
confidence: 96%
“…The figures show a near linear dependence of these parameters on each other with a slope of almost unity indicating a power law dependence of dc on H of the form 𝜎 𝑡 ∝ 𝜔 𝐻 𝑛 where n is the slope of the graph. This implies that the dc and ac conductivity are correlated in AHR [57].…”
Section: Resultsmentioning
confidence: 96%
“…Using Scherer's formula, the average crystallite size was calculated to be in the 40-50nm range [16]. The structure with a smaller particle size or a large grain boundary has more oxygen vacancies resulting in higher conductivity [13,19,38]. The Energy-Dispersive Spectroscopy (EDS) study, shown in Figure 4, shows all the atomic constituents and their atomic percentage.…”
Section: A Structural and Morphological Propertiesmentioning
confidence: 99%
“…In SOFCs, LaAlO 3 may be a good alternative perovskite candidate for the oxide ions conductor (electrolyte) [16][17][18]. However, in an oxidizing environment, pure LaAlO 3 has lower ionic conductivity and more flexible conduction behavior [19]. The ionic conductivity of electrolytes can be best used through composition change by choosing a suitable aliovalent dopant and its optimum concentration [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors such as the shape and density of grain boundaries, the structural disorders, and the presence of impurities in the electrolyte powders can affect the grain boundary resistance of the dense electrolyte pellets [14]. Moreover, the applied synthesis method, the processing conditions, and the dopant concentration and composition can change the properties of the sintered electrolytes and grain boundaries [15].…”
Section: Introductionmentioning
confidence: 99%